Effectiveness of mirror therapy by Fugl-Meyer scale in stroke: review with meta-analysis - de Carvalho, Marcelo Silva; Oliveira, Luís Henrique Sales (Seven Editora, 2023)
of Mirror Therapy (MT) compared to the various types of Control Groups (CGs) by the Fugl-Meyer Scale (FMS) in patients with stroke. Method: a systematic review was performed with meta-analysis of randomized controlled trials in the LILACS, MEDLINE, Cochrane Library and PEDro databases (2008-2018). Controlled studies of patients with strokes who underwent treatment with TM were included and excluded animal studies, incompatible subjects, incomplete data, case studies and absence of total FMS scores (upper and lower extremities). Results: The search resulted in 193 studies and, after the selective steps, nine articles remained; of these, eight analyzed the upper extremity and one lower extremity. All studies analyzed together showed high heterogeneity and, when investigated in dissociation, such fact did not occur. The data did not show significant differences between the comparison of MT and CGs, when FMS was used by the global evaluation of the members (95% CI: -0.59 to 0.88) and the separate evaluation of the upper extremity (95% CI: -0.96 to 0.53). The lower extremity in relation to the CGs showed significant results. Conclusion: There is a lack of clear evidence to support the superiority of the MT by the analysis of the FMS before the CGs. DOI: https://doi.org/10.56238/colleinternhealthscienv1-007